Atypical forms of employment in the control practice of the National Labour Inspectorate - Kopeć, Bartosz (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
Specific challenges of the labour market in the recent years favor the evolution of new forms of performance and organization of work, also known as atypical employment. Undoubtedly, the new solutions, together with the progressing robotization and algorithmization, currently constitute one of the most important challenges for the labour market as their emergence provides for a number ofopportunities and threats, for both workers and employers.It should be emphasized that non-typical employment contributes to making the labour market andnew forms of professional activity more attractive, but on the other hand, it hinders respecting andprotection of workers’ rights. Therefore, besides analyzing the pros and cons of new forms of working,it is necessary to raise the awareness of the fact that the lack of appropriate legislation not onlylimits the protection of the stakeholders but also prevents the activities of inspection authorities,including the National Labour Inspectorate.The importance of the issue is highlighted by the fact that the topic constitutes a challenge not onlyfor Poland but also other EU Member States and other countries around the world. In this context,particular emphasis should be placed on the proposed Directive of the European Parliament and ofthe Council on improving working conditions in platform work, which could serve as the basis fordiscussions on national-level solutions.